Collaborative Approaches to Basic Service Delivery in IKN: Engaging Stakeholders for Sustainable Development - Suwito, Suwito (Faculty of Public Health Mulawarman University, Indonesia, 2025)
The development of the Nusantara Capital City (IKN) presents a unique opportunity to implement innovative approaches to sustainable development. This research investigates the role of collaborative partnerships in ensuring the effective delivery of basic services within the IKN. By analyzing the experiences of various stakeholders, this study identifies the key factors that contribute to successful collaboration and the challenges that hinder progress. The findings of this research can inform the development of more sustainable and resilient cities in Indonesia and beyond. This study examines the application of collaborative approaches in delivering basic services within the Nusantara Capital City (IKN) project. By engaging a wide range of stakeholders, including government agencies, private sector, and local communities, the research aims to explore the potential of collaborative partnerships in achieving sustainable development goals. This paper will discuss the key challenges and opportunities associated with implementing collaborative approaches, and provide recommendations for enhancing stakeholder engagement and coordination.